2017
DOI: 10.1128/jvi.01521-16
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Porcine CD163 Scavenger Receptor Cysteine-Rich Domain 5 with a CD163-Like Homolog Confers Resistance of Pigs to Genotype 1 but Not Genotype 2 Porcine Reproductive and Respiratory Syndrome Virus

Abstract: CD163 knockout (KO) pigs are resistant to infection with genotype 2 (type 2) porcine reproductive and respiratory syndrome virus (PRRSV). Furthermore, the substitution of CD163 scavenger receptor cysteine-rich (SRCR) domain 5 with a homolog of human CD163-like (hCD163L1) SRCR 8 domain confers resistance of transfected HEK cells to type 1 PRRSV. As a means to understand the role of domain 5 in PRRSV infection with both type 1 and type 2 viruses, pigs were genetically modified (GM) to possess one of the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 30 publications
7
86
0
Order By: Relevance
“…The recovery of porcine alveolar macrophages is described in Wells et al (2017). Lungs were removed from euthanized pigs and lavaged by pouring 100 ml of cold PBS into the trachea.…”
Section: Anpep Ko Pigs Viruses and Cellsmentioning
confidence: 99%
“…The recovery of porcine alveolar macrophages is described in Wells et al (2017). Lungs were removed from euthanized pigs and lavaged by pouring 100 ml of cold PBS into the trachea.…”
Section: Anpep Ko Pigs Viruses and Cellsmentioning
confidence: 99%
“…Truncation assays have demonstrated that the SRCR5 domain of pCD163 is required for PRRSV infection [46], results further supported by the fact that genome-edited pigs bearing CD163 lacking SRCR5 were resistant to viruses of both PRRSV-1 and PRRSV-2 [47]. However, it is notable that replacement of the SRCR5 domain of pCD163 with the SRCR5 domain of the human CD163-like homolog (CD163Li) only conferred resistance to strains of PRRSV-1, but not to PRRSV-2 [48], implying different preferred receptor utilization between PRRSV-1 and PRRSV-2 strains. Moreover, macrophages play a pivotal role in the host immune system as macrophage subset is specialized in function and reflected by the expression of different receptors such as complement receptors, Fc-receptors, adhesion molecules, and receptors for various soluble mediators [49].…”
Section: Discussionmentioning
confidence: 90%
“…The scavenger receptor cysteine‐rich domain 5 (SRCR5) region of CD163 was shown to be an interaction site for the PRRSV in vitro. To explore the function of domain 5 in PRRSV infection, genetically modified pigs with a normal SRCR domain 5 or the SRCR domain 5 replaced with a synthesized exon encoding a homolog of the hCD163L1 SRCR domain 8 (domain swap) were generated by CRISPR/Cas9 technology (Burkard et al, ; Wells et al, ). Infection studies with different PRRSVs revealed that CD163 is likely to be the receptor for all PRRS viruses and that domain 5 knockout pigs are resistant to these viruses (Wells et al, ).…”
Section: Crispr‐based Genome Editing In Biomedical Investigationmentioning
confidence: 99%
“…To explore the function of domain 5 in PRRSV infection, genetically modified pigs with a normal SRCR domain 5 or the SRCR domain 5 replaced with a synthesized exon encoding a homolog of the hCD163L1 SRCR domain 8 (domain swap) were generated by CRISPR/Cas9 technology (Burkard et al, ; Wells et al, ). Infection studies with different PRRSVs revealed that CD163 is likely to be the receptor for all PRRS viruses and that domain 5 knockout pigs are resistant to these viruses (Wells et al, ). Refining the modification of CD163 provides the opportunity to breed pigs that are resistant to PRRS while retaining the important biological functions associated with CD163 (Burkard et al, ).…”
Section: Crispr‐based Genome Editing In Biomedical Investigationmentioning
confidence: 99%